Dependence of Harvest Structure and Productivity of Pea Varieties on Forage Area Approval - Mirsharipova Guljaxon Kamalovna (Zien Journals, 2022)
The article discusses the effect of planting strategies on plant production elements and productivity when peas are planted in october in the Sirdarya region's weakly saline soils. The variety of samples of peas” Uzbekistan-32 " (control) FLIP 98-140c-(Guldu-Tashdau), FLIP 98-1116c-(Miroz), FLIP 98-152C and FLIP 98-183s-(Khalima) when sowing in 60x10x1, 60x15x1, and 60x20x1 systems, the quantity and mass of pods and grains yield elements were greater in the 60x20x1 system. On the contrary, the reduction in food area resulted in a drop in the number of grains per plant, which had a favorable influence on grain size. The mass of 1000 grains was 69-128 g more in all analyzed pea samples than in the control, but the grain was larger in the FLIP 98-183s-(Halima) sample than in all other kinds, with a mass of 1000 grains of 403-388 g. According to the data acquired, the grain yield of pea types is higher when planted densely (60x10x1). Pea samples FLIP 98-140c-(GulSU-TashSAU) (25-36.1 ts/ha) and FLIP 98- 1116c-(MirOZ) (25.4-39 ts/ha) produced the best yield
Keywords: Uzbekistan; FLIP; crop structure; pod number